(untitled) (Sevana: Jurnal Pengabdian Kepada Masyarakat, 2023)
Artificial Intelligence-based learning media is a virtual character service with artificial intelligence or AI that imitates human conversation via voice messages, text chat or both. Artificial Intelligence-based learning media applications can cover the needs in the world of education today, especially in finding solutions or finding the best solution in solving a problem, but many students do not understand what technologies can be utilized in learning activities and the benefits of using them. technology in the world of education today. The main target of this Community Service (PKM) is the students of MTS Bany Tsamin, Teluk Terate Village, Kramatwatu District, Serang Regency, the students need to know about technology that can be utilized in the world of education as well as the use of existing technology, one of which is the use of technology based on Artificial Intelligence technology to be used as a learning medium. This Community Service activity was carried out by the Community Service (PKM) team from the Information Systems, Information Management and Accounting Computerization Study Program to share knowledge about various training courses in creating and utilizing Artificial Intelligence-based technology. With this PKM activity, it is hoped that students will be able to know about Artificial Intelligence technology and be able to use it in learning at school.